Nurses’ Knowledge and Practices concerning Physiotherapy Protocol at Intensive Care Units in AL-Nasiriyah City - waheed, noor (Iraqi National Journal of Nursing Specialties, 2022)
Abstract: Objective (s): This study aims to assess nurses’ knowledge and practice regarding physiotherapy protocol at intensive care units Methodology: descriptive cross-sectional study design executed at the ICU in the city hospitals of AL- for the time of 13th October/ 2021 to 7th April /2022. Questionnaire filled by 75 nurses who work in ICU who had chosen by non-probability (purposive) selection collected the data. Then the researcher used an observational checklist to evaluate nurses’ practice. The data was analyzed using descriptive statistics and SPSS. Results: the study found a deficit in nurses’ knowledge and practices regarding physiotherapy protocol in intensive care units. The nurses are not fully familiar with physiotherapy techniques, which is reflected in the low level of performance. Recommendations: Providing an educational program to increase nurses’ knowledge and practices regarding physical therapy techniques. Making another studies on physical therapy in other settings.